Syirkah tanpa tatap muka: Analisis fiqih atas kerja sama virtual di era ekonomi digital - Muti, Farah Auliya (Maliki Interdisciplinary Journal, 2025)
The validity and application of non-face-to-face syirkah contracts conducted through digital platforms such as messaging applications, marketplaces, and social media. In the digital economy, virtual cooperation is increasingly common without physical presence, raising fiqh issues related to the validity of ijab qabul, contract certainty, potential gharar, and risk sharing mechanisms. This study uses classical and contemporary fiqh mu'amalah approaches to assess whether virtual syirkah contracts can be categorized as valid, as well as the sharia requirements that must be met so that digital cooperation remains in accordance with the principles of fairness, transparency, and protection from fraud. The analysis shows that non-face-to-face syirkah is permissible as long as the contract is made clearly, using verifiable communication media,6 and fulfills the pillars and conditions of syirkah in accordance with the provisions of the scholars.